Phylogenetic studies of magnoliids: Advances and perspectives - Shen, Zhiguo; Ding, Xin; Cheng, Jianming; Wu, Fangfang; Yin, Hengfu; Wang, Minyan (Frontiers in Plant Science, 2023)
Magnoliids are the largest flowering plant clades outside of the eudicots and monocots, which are distributed worldwide and have high economic, ornamental and ecological values. Eudicots, monocots and magnoliids are the three major clades of Mesangiospermae, and their phylogenetic relationship is one of the most interesting issues. In recent years, with the continuous accumulation of genomic information, the evolutionary status of magnoliids has become a hot spot in plant phylogenetic research. Although great efforts have been made to study the evolution of magnoliids using molecular data from several representative species such as nuclear genome, plastid genome, mitochondrial genome, and transcriptome, the results of current studies on the phylogenetic status of magnoliids are inconsistent. Here, we systematically describe the current understanding of the molecular research on magnoliid phylogeny and review the differences in the evolutionary state of magnoliids. Understanding the research approaches and limitations of magnoliid phylogeny can guide research strategies to further improve the study of the phylogenetic evolution of magnoliids.